Effect of Different Inorganic Substrates on Growth Performance of African Catfish (Clarias gariepinus, Burchell 1822) and Lettuce (Lactuca sativa L.) - Murat Yeşiltaş; Mehmet Ali Turan Koçer; Hüseyin Sevgili; Edis Koru (Turkish Journal of Agriculture: Food Science and Technology, 2021)
Lettuce (Lactuca sativa L.) and African catfish (Clarias gariepinus) were preferred to grow in aquaponics due to their high and fast productivity growth. However, limited research was conducted on the impact on different inorganic substrates’ growth performance in aquaponics. In this study, lettuce’s growth performance was determined in four different kinds of inorganic substrates in Nutrient Film Technique (NFT) aquaponics by measuring final weight, daily growth rate, stem diameter, plant and root lengths, leaf number per plant and shoot/root ratio. Polyester fiber, rock wool, zeolite, and gravel were used as inorganic substrate materials. A constant flow rate of 0.3 L/min was maintained using with a submersible pump motor. At the end of the study, the African catfish’s feed conversion ratio was estimated to be 0.66, while the specific growth rate (SGR) was 2.3%. Total lettuce yields for polyester fiber, rock wool, zeolite and gravel were obtained as 5.072,22 kg/m2, 4.934,03 kg/m2, 6.067 kg/m2, and 5.382,64 kg/m2 respectively. There were statistically significant differences for daily growth rate between the inorganic substrates that the significantly highest values were recorded in the zeolite. The results revealed that initial plant length and shoot/root ratio were the significant factors on the growth performance for lettuce in aquaponic system tested. The best lettuce yield performance was observed in zeolite substrate but, economically available option was found as gravel for hydroponic troughs.